(untitled) (World Bulletin of Education and Learning, 2026)
This paper examines the development of students’ historical knowledge as a socio-pedagogical problem through the prism of the pedagogical legacy of the Enlightener Jadids who emerged in early twentieth-century Turkestan. The study argues that the Jadid program of national awakening, educational reform, revitalization of historical memory, and cultivation of national consciousness strengthens the educational and civic mission of history teaching in higher education. Under globalization, fragmented and superficial historical learning, weak engagement with national history, and underdeveloped historical reasoning are identified as key risk factors; in response, the article outlines the methodological potential of Jadid pedagogy for restoring the integrative link between education and upbringing. On the basis of the views of Mahmudhoja Behbudiy, Abdulla Avloniy, Munavvarqori Abdurashidxonov, and Abdurauf Fitrat, history is conceptualized as a “mirror of the nation” and as a formative discipline that connects historical understanding with moral education, civic responsibility, and social agency. The Jadids’ principles—linking content to real life, replacing rote memorization with analysis, comparison, and reasoned conclusions, and balancing national and universal values—are interpreted as conceptually aligned with competency-based, learner-centered, activity-oriented, and constructivist approaches. The paper concludes that integrating Jadid pedagogical ideas into contemporary history instruction can enhance the social relevance of the discipline, position students as active subjects of learning, and promote historical consciousness, national memory, and critical thinking.